Lack of effect of bioactive‐rich extracts of pomegranate, persimmon, nettle, dill, kale and Sideritis and isolated bioactives on platelet function. (12th June 2013) - Hollands, Wendy J; Saha, Shikha; Hayran, Osman; Boyko, Nadiya; Glibetic, Maria; Konic‐Ristic, Aleksandra; Jorjadze, Mariam; Kroon, Paul A
Abstract BACKGROUND The health benefits of fruit and vegetable‐rich diets may be partly due to modulation of platelet activity by bioactive phytochemicals. The aim of this study was to investigate the effects of bioactive‐rich plant extracts and isolated bioactive metabolites on platelet function. Blood samples (n =15 subjects) were treated with extracts of bioactive‐rich plants consumed as traditional foods in the Black Sea region, or with human metabolites of the bioactives quercetin and sulforaphane. Platelet function was assessed using the PFA‐100. RESULTS None of the extracts containing various flavonoids, glucosinolates and other bioactives, or isolated bioactive metabolites of quercetin or sulforaphane, caused significant changes in PFA‐100 closure time (CT). In contrast, the positive controls (aspirin and Abciximab) consistently caused significant increases in CT for the platelet agonists epinephrine and ADP, respectively. CONCLUSION These data do not support the notion that these plant bioactives can improve human platelet function. © 2013 Society of Chemical Industry